Occurrence, removal, and toxicity of pharmaceutical compounds in the selected drinking water sources of Istanbul - Saner, Samim. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2023., 2023)
Pharmaceutical compounds (PCs) after being ingested reach water bodies through the excreta of humans and animals, and depending on the effectiveness of treatment systems, they can end up in drinking water sources, posing a significant threat to public health. In this dissertation; occurrence, removal, fate and cytototoxicity of some PCs were investigated in the raw and treated drinking water samples collected from different water sources of Istanbul. In the first part of the study, 55 PCs were analyzed in all water samples collected from 13 drinking water treatment plants (DWTP) in Istanbul, and 17 PCs were quantified. At least one or more PCs were determined in 77% of all samples. On average 70% of PCs found in raw water was eliminated in DWTPs. In 80% of the samples where PCs were detected, the parent pharmaceutical molecules have been degraded with a removal efficiency exceeding 99%. In the second part, the extent of degradation of PCs were investigated on three molecules; sulfamethoxazole, carbamazepine, and clarithromycin. The main result is that all three tested pharmaceuticals were completely degraded into other organic transformation products after treatment. In the third part, cytotoxicity of degradation products were investigated on human liver (HepG2) and human kidney (HK-2) cells. Significant cytotoxicity was observed in HK-2 and HepG2 cells after treatment in distilled water, whereas in raw water the observed cytotoxic activity disappeared. All these suggest toxicity of degradation products of PCs generated in DWTPs need to be considered comprehensively in the risk assessment, process design and optimization.
Keywords: Drinking water -- İstanbul.; Drugs -- Dosage forms.; Public health -- Environmental aspects.